Universal Transfer of Word Meaning – Metaphor and Metonymy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article we study one of the stylistic devices as metaphor and metonymy. Comparing and studying Russian and French, we see that French is filled with metaphors, almost consists of them. Metaphors and metonymies exist in it not only as a means of expression, although the most important, but also as grammatical means of constructing sentences.